A Comparative Application for Evaluating Composite Fabrics Used in Electromagnetic Shielding - Kizilcay Abdulla, F. G.; Abdulla, R. (Engineering, Technology & Applied Science Research, 2017)
Composite fabrics containing metal filaments are used widely for preventing electromagnetic radiation. Many experiments involving them are carried out continuously. Results are simulated in order to analyze their performance. Coding in Matlab is a popular method to compare the electromagnetic shielding properties of composite fabrics but for different options Matlab codes must be edited each time. Scientists who are not experts in coding have difficulties on editing such codes. To overcome this, an application written in C# in Visual Studio with .Net platform was developed. This application is integrated with Bunifu, which allows the application to be well designed. The proposed interface is user friendly and lets the user choose the available fabric with its stitch length from panel section. By setting options one can get the electromagnetic parameters such as scattering (S) parameters, reflection, transmission and absorption coefficients and total shielding effectiveness (SE) values with one click. As the application is integrated with Matlab codes, output is given as a Matlab graph with desired options. In this way the distinctions between the chosen fabrics can be analyzed easily.